A cross-sectional study on utilisation and content of antenatal services among pregnant women in a coastal area of Thrissur district - M. V., Sruthi; Raphael, Bablu (International Journal Of Community Medicine And Public Health, 2017)
Background: Antenatal care is ‘care before birth’ to promote wellbeing of mother and foetus. The number of antenatal care visits and the timing of the first visit are important for the health of the mother and the outcome of the pregnancy. The use of ANC varies from country to country considerably, with underutilization among pregnant women, in low income countries like Asia & Africa. Within the country ANC utilization varies with mother’s age, education, occupation, income, parity, place of residents, availability and cost of services. In coastal areas most of the people belong to fisherman community and their socio-demographic characteristics are different from that of other areas. Not enough studies have been conducted previously; in coastal areas to obtain data on utilization of ANC services. It is in this background that the present study was carried out to assess the utilization and content of antenatal services among pregnant women in a coastal area. Methods: A cross-sectional study was conducted in Kadappuram gramapanchayath, Chavakkad Taluk, during the period of December 2013 to March 2014. Data collection was done by interviewing total 286 registered mothers from four subcentres from Kadappuram CHC, using a pretested validated questionnaire. Results: Out of 286 mothers, 179 (62.6%) of pregnant mothers had taken optimum antenatal care and remaining 107 (37.4%) of mothers had taken sub-optimum antenatal care. Among utilisation and content of antenatal services, only 228 (79.7%) of pregnant mothers done the Hb estimation and blood screening in first trimester itself. The proportion of mothers consumed 100 IFA tablets were 279 (89.5%), but 30 (10.5%) mothers had not taken full course of IFA tablets. Only 202 (70.6%) of mothers received the advice on family planning method during their antenatal visits and remaining 84 (29.4%) mothers did not received any advice. There was a statistically significant difference between socio-economic status of pregnant mothers and services like family planning advice and Hb estimation and screening at first trimester. Conclusions: The study revealed that, even though all the pregnant women were literate and majority had educational status up to high school, the antenatal services like routine blood examination in the first trimester, Iron and folic acid coverage and advice on family planning services were relatively low. Improving the socio-economic status of pregnant women would improve the utilization and content of antenatal care. The study also emphasizes the need for awareness programs for antenatal mothers on content and utilisation of proper ANC.